2013
DOI: 10.1016/j.jtcvs.2013.07.031
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes and fate of the distal aorta following 1-stage repair of extensive chronic thoracic aortic dissection

Abstract: Our extended experience with the 1-stage procedure confirms its safety and feasibility for treatment of extensive chronic thoracic aortic dissection. It is associated with a low incidence of reoperation on the contiguous aorta for aneurysmal degeneration. It represents a viable alternative to 2-stage and hybrid procedures that are also used to treat this condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Furthermore, many patients do not return for the second operation. [8][9][10][11] They might die due to rupture of the residual aortic lesions while awaiting second procedures or comorbidities preclude another procedure through a lateral thoracotomy. 12 In contrast, the risk of spinal cord complications may be reduced by staged operations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, many patients do not return for the second operation. [8][9][10][11] They might die due to rupture of the residual aortic lesions while awaiting second procedures or comorbidities preclude another procedure through a lateral thoracotomy. 12 In contrast, the risk of spinal cord complications may be reduced by staged operations.…”
Section: Discussionmentioning
confidence: 99%
“…Very few reports have been published regarding 1-stage replacement from the aortic arch to thoracoabdominal aorta. 11,18,19 Svensson and colleagues 20 reported a successful case in a 68-year-old patient who underwent replacement of the entire aorta from the aortic valve to the aortic bifurcation via deep hypothermia with circulatory arrest and retrograde perfusion of the brain. Massimo and colleagues 6 reported that 7 patients underwent replacement of the aorta from aortic valve to bifurcation.…”
Section: Discussionmentioning
confidence: 99%
“…The need for a retrograde deployment of an additional stent graft in a second stage procedure as well as the high costs would complete the list of differences between this hybrid procedure and conventional surgery. On the other hand, the updated results after Kouchoukos's one-stage repair of extensive chronic thoracic aortic dissection demonstrated that, in addition to excellent surgical results, there is a very high freedom from reoperation for aneurysmal growth of the distal aorta [6].…”
Section: Discussionmentioning
confidence: 99%
“…One-stage open repair is conventional but serves as a definitive procedure for this complicated subset of patients. Kouchoukos et al 2 described 68 recent cases of one-stage open repair using bilateral thoracotomy with successful results. The hospital mortality rate was only 2.9%, and permanent paraplegia occurred in only 1.5% of total cases.…”
Section: Discussionmentioning
confidence: 99%